2015
DOI: 10.1590/2359-3997000000022
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid disorders are common in first-degree relatives of individuals with type 1 diabetes mellitus

Abstract: Objective: Thyroid diseases are common in individuals with type 1 diabetes mellitus (T1DM) and should be investigated annually in these individuals. The aim of this study was to evaluate the frequency of thyroid diseases in first degree relatives (FDR) of patients with T1DM. Subjects and me thods: Eighty individuals (40 patients with T1DM and 40 FDR) were interviewed and blood was sampled for thyroid-stimulating hormone (TSH), free thyroxine (FT4) and thyroid peroxidase (TPO) antibodies measurement. Autoantibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The risk is slightly greater if one has a first-degree relative (mother, sister, and daughter) with TD. 32 However, others report that a positive family history of any form of TD may not be associated with increased risk of developing ID or hypothyroidism. 33 The present study found a positive correlation.…”
Section: Discussionmentioning
confidence: 99%
“…The risk is slightly greater if one has a first-degree relative (mother, sister, and daughter) with TD. 32 However, others report that a positive family history of any form of TD may not be associated with increased risk of developing ID or hypothyroidism. 33 The present study found a positive correlation.…”
Section: Discussionmentioning
confidence: 99%
“…The concomitant presentation of T1DM and another autoimmune disorder may complicate diabetes management and result in varying clinical symptoms, thus seriously influencing patient quality of life[ 6 ]. Among these additional autoimmune disorders co-occurring among children and adolescents with T1DM, autoimmune thyroid disease (AITD) accounts for the highest proportion[ 7 ]. As the most prevalent organ-specific immune-mediated disorder in the world, AITD is characterized by autoreactive lymphocyte infiltration in the thyroid and the presence of autoantibodies targeting thyroid antigens[ 8 ].…”
Section: Introductionmentioning
confidence: 99%